An Investigation into the Spatial Disparities in Development Quality and the Influence Mechanism of the Private Economy in Hunan Province, China - Liu, Daobo; Zhang, Siqi (Journal of Theory and Practice in Economics and Management, 2024)
The private economy, as a cornerstone of economic development, plays a crucial role in addressing the economic challenges faced by Hunan Province, China. Investigating the impact of innovation investments and human capital on the development of the private sector is essential for fostering the growth of the private economy in Hunan Province. This paper examines the spatial disparities in the quality of private economic development within Hunan Province and explores the underlying mechanisms using the spatial Durbin model. The findings indicate that: First, there are significant differences in the development of the private economy between the eastern and western regions of Hunan, with the western region developing at a slower pace compared to the eastern region. Second, both innovation investment and human capital significantly influence the development of the private economy; however, innovation investment exhibits a negative spillover effect. In conclusion, increasing investment in innovation and human capital, reducing regional disparities, and enhancing coordinated development among cities will contribute to the stable and sustainable development of the private economy in Hunan Province.